Global Trends in Higher Education and Learning Technology: A Comprehensive Bibliometric Study - Saleng, Syamsidar; Yaumi, Muhammad; Sukmawati, Sukmawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study examines the decade-long development of research on independent learning, higher education, and learning technology from 2016 to 2025, addressing the lack of a holistic synthesis that integrates trends, collaboration patterns, and thematic evolution in this interdisciplinary field. Using a bibliometric approach, data were extracted from the Scopus database (n = 697) and analyzed through VOSviewer and Biblioshiny to map the intellectual, conceptual, and social structures of the domain. The results reveal a substantial increase in research output, particularly between 2022 and 2024, with China, Indonesia, and Malaysia emerging as leading contributors and authors such as Zhang X. and Wang X. playing central roles. Influential publication venues include the International Journal of Educational Technology in Higher Education and Sustainability. Keyword analyses highlight dominant themes such as higher education, e-learning, and artificial intelligence, alongside emerging topics including ChatGPT, gamification, and machine learning, indicating a shift toward personalized and intelligent learning environments. These findings underscore the accelerating global transformation of technology-enhanced education and point to the need for further research that integrates pedagogical, technological, and policy perspectives to support the development of adaptive and equitable learning ecosystems.